Murder State : California's Native American Genocide, 1846-1873 - Lindsay, Brendan C. (Book collections on Project MUSE., 2012)
"In the second half of the nineteenth century, the Euro-American citizenry of California carried out mass genocide against the Native population of their state, using the processes and mechanisms of democracy to secure land and resources for themselves and their private interests. The murder, rape, and enslavement of thousands of Native people were legitimized by notions of democracy--in this case mob rule--through a discreetly organized and brutally effective series of petitions, referenda, town hall meetings, and votes at every level of California government. Murder State is a comprehensive examination of these events and their early legacy. Preconceptions about Native Americans as shaped by the popular press and by immigrants' experiences on the overland trail to California were used to further justify the elimination of Native people in the newcomers' quest for land. The allegedly 'violent nature' of Native people was often merely their reaction to the atrocities committed against them as they were driven from their ancestral lands and alienated from their traditional resources"--Provided by publisher